CCAFS/FAO Expert Workshop on Smallholder Mitigation: Whole Farm and Landscape Accounting. Rome, 27-28 October 2011. Workshop Summary - CGIAR Research Program on Climate Change, Agriculture and Food Security; Food and Agriculture Organization of the United Nations (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2011)
Summary Report from the workshop held in Rome 27-28 October 2011